1999
DOI: 10.1161/01.atv.19.5.1267
|View full text |Cite
|
Sign up to set email alerts
|

Lovastatin Decreases the Receptor-Mediated Degradation of Acetylated and Oxidized LDLs in Human Blood Monocytes During the Early Stage of Differentiation Into Macrophages

Abstract: Abstract-3-Hydroxy-3-methylglutaryl-coenzyme A reductase inhibitors are used therapeutically to upregulate the LDL receptor-mediated removal of plasma cholesterol by the liver. Several lines of evidence indicate that these drugs also exert direct effects on the metabolism of native and modified LDL in extrahepatic cells. We studied the effects of lovastatin (LOV) on the degradation of native, acetylated, and oxidized LDL, and on levels of mRNA encoding for the LDL, types I and II class A macrophage scavenger, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
1

Year Published

2000
2000
2010
2010

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(27 citation statements)
references
References 62 publications
1
25
1
Order By: Relevance
“…Previous studies evaluated statin action on scavenger receptor expression in cultured human blood monocytes. Thus, lovastatin decreased the expression of CD36 mRNA during the early stages of the differentiation of these cells into macrophages, pitavastatin reduced CD36 surface protein expression in a human monocyte cell line (THP1 cells) and in human monocyte-derived macrophages, isolated from healthy donors 14,15) . Finally, atorvastatin treatment for one month decreased the CD36 gene expression in a culture of differentiating monocytes from hypercholesterolemic patients 16) .…”
Section: Discussionmentioning
confidence: 92%
“…Previous studies evaluated statin action on scavenger receptor expression in cultured human blood monocytes. Thus, lovastatin decreased the expression of CD36 mRNA during the early stages of the differentiation of these cells into macrophages, pitavastatin reduced CD36 surface protein expression in a human monocyte cell line (THP1 cells) and in human monocyte-derived macrophages, isolated from healthy donors 14,15) . Finally, atorvastatin treatment for one month decreased the CD36 gene expression in a culture of differentiating monocytes from hypercholesterolemic patients 16) .…”
Section: Discussionmentioning
confidence: 92%
“…Lovastatin was also shown to decrease expression of CD36 and the type A scavenger receptor in human bloodderived monocytes in culture for 2 and 5 days but not in more mature macrophages. 37 Finally, monocyte-derived macrophages had decreased expression of CD36 and the type A scavenger receptor in hypercholesterolemic patients treated with atorvastatin relative to monocyte-derived macrophages from untreated patients. 38 However, in these studies, no molecular mechanisms were identified by which statins decreased scavenger receptor expression.…”
Section: Discussionmentioning
confidence: 94%
“…These include inhibition of cell adhesion to endothelium [71], cell growth induced by oxidized LDL [63], cell expression of matrix metalloproteinase [19] and scavenger receptors [31], and LDL oxidation and uptake [5]. All these cellular events may slow down cholesterol accumulation in macrophages and reduce plaque stability and atherosclerotic development.…”
Section: Discussionmentioning
confidence: 99%